Assessing University Libraries in Uttar Pradesh with Emphasis to Infrastructure and Information and Communication Technology Applications - Shukla, Archana (DESIDOC Journal of Library & Information Technology, 2015)
Academic libraries are confronted with the challenges of change. The aim of the present study is to investigate the prevalent scenario and status of university libraries (Central and State) in Uttar Pradesh in terms of collection, budget, manpower, and a special reference to ICT infrastructure. For the purpose of this study questionnaire is used as the tool to collect data from university libraries. It highlights different facets of libraries in the state only. The study reveals that libraries do not have proper infrastructure. The study is restricted to a limited number of university libraries in the state. Findings of the study will facilitate the authorities to take appropriate measures in improving the condition of the libraries in the State.